2014
DOI: 10.1111/eff.12120
|View full text |Cite
|
Sign up to set email alerts
|

Density‐dependent territory size and individual growth rate in juvenileAtlantic salmon (Salmo salar)

Abstract: Whether territoriality regulates population size depends on the flexibility of territory size, but few studies have quantified territory size over a broad range of densities. While juvenile salmonids in streams exhibit densitydependent mortality and emigration, consistent with space limitation, there has been relatively little study of how territory size and individual growth rate change over a broad range of densities, particularly in field experiments. Consequently, we manipulated the density (range = 0.25-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 47 publications
5
20
0
Order By: Relevance
“…The studies referred to above suggested that density-dependent growth is more intensive in less mobile groups with high survival of individuals due to strong competition for space and food and with a relatively low chance for individuals to achieve ideal free distribution (sensu Fretwell & Lucas 1969). Competition is generally divided into exploitative and interference interactions (Krebs & Davies 1987), but the importance of these interactions in the regulation of density-dependent growth in salmonids is ambiguous (Imre et al 2005(Imre et al , 2010Ward et al 2007;Lindeman et al 2015). Population density on the large scale (several kilometres or the whole stream) can causes depletion of resources and changes the growth of individuals throughout exploitative competition.…”
mentioning
confidence: 99%
“…The studies referred to above suggested that density-dependent growth is more intensive in less mobile groups with high survival of individuals due to strong competition for space and food and with a relatively low chance for individuals to achieve ideal free distribution (sensu Fretwell & Lucas 1969). Competition is generally divided into exploitative and interference interactions (Krebs & Davies 1987), but the importance of these interactions in the regulation of density-dependent growth in salmonids is ambiguous (Imre et al 2005(Imre et al , 2010Ward et al 2007;Lindeman et al 2015). Population density on the large scale (several kilometres or the whole stream) can causes depletion of resources and changes the growth of individuals throughout exploitative competition.…”
mentioning
confidence: 99%
“…Capacity was based on the space-limited concept of population regulation in salmonids, in which territorial juveniles each require a minimum area of habitat that is a function of body size (Chapman, 1966;Dunham & Vinyard, 1997;Lindeman, Grant, & Desjardins, 2015;Rosenfeld, 2014;Smith, Baumgartner, Suthers, Fielder, & Taylor, 2013;Steingrimsson & Grant, 1999). Capacity was based on the space-limited concept of population regulation in salmonids, in which territorial juveniles each require a minimum area of habitat that is a function of body size (Chapman, 1966;Dunham & Vinyard, 1997;Lindeman, Grant, & Desjardins, 2015;Rosenfeld, 2014;Smith, Baumgartner, Suthers, Fielder, & Taylor, 2013;Steingrimsson & Grant, 1999).…”
Section: Steelhead Smolt-production Capacitymentioning
confidence: 99%
“…Hutchins, Engel, Nowlin, & Schwartz, 2016;Kuehne & Olden, 2016;Lindeman, Grant, & Desjardins, 2014). Hutchins, Engel, Nowlin, & Schwartz, 2016;Kuehne & Olden, 2016;Lindeman, Grant, & Desjardins, 2014).…”
Section: Statistical Analysesmentioning
confidence: 99%